Usefulness of fusion images of unenhanced and contrast-enhanced arterial phase cone-beam CT in the detection of viable hepatocellular carcinoma during transarterial chemoembolization - Kim, Eu Hyun (Diagn Interv Radiol, 2018)
PURPOSE: We aimed to evaluate the diagnostic efficacy of fusion imaging of unenhanced and arterial phase contrast-enhanced cone-beam computed tomography (CBCT) by comparing with multidetector computed tomography (MDCT) in detection of viable hepatocellular carcinoma (HCC) in patients who have been previously treated with transarterial chemoembolization (TACE). METHODS: In this retrospective study, a total of 173 tumors in 33 known HCC patients (21 men, 12 women; mean age, 64±7.6 years; mean tumor size, 2.15±1.70 cm) who had been previously treated with TACE and underwent additional session of TACE were included. The sensitivity and positive predictive values of preprocedural MDCT and fusion CBCT for detection of viable tumor were analyzed with follow-up MDCT images performed 3–4 weeks after TACE, as reference standard. RESULTS: A total of 141 remote and 32 marginal viable tumors were included. The sensitivities for detection of remote, marginal, and total viable tumors were 80.9%, 68.8%, and 78.6% for MDCT and 96.5%, 96.9%, and 96.5% for fusion CBCT, respectively. The positive predictive values for detection of remote, marginal, and total viable tumors were 95.0%, 78.6%, and 95.8% for MDCT, and 97.1%, 88.6%, and 97.7% for fusion CBCT, respectively. Fusion CBCT showed statistically higher sensitivity and positive predictive value for detection of viable tumors (P < 0.001). CONCLUSION: The diagnostic performance of fusion imaging of unenhanced and contrast-enhanced arterial phase CBCT was superior to MDCT for detection of viable HCCs.